Pentingnya Keamanan Data Dalam Intelijen Bisnis - Ari Sahputra; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
Digital transformation is technology-induced change at many levels in an organization that includes the exploitation of digital technologies to improve existing processes, and the exploration of digital innovation, which has the potential to change business models. Business intelligence consists of the use of various tools and methods that enable and assist and organization in the collection of relevant data and information from internal and external sources. This research is a type of library research, namely research whose object of study uses library data in the form of books or scientific articles as the data source. The data collection techniques in this research are based on digital literacy from previous research. The data analysis technique in this research was carried out by reading, reviewing and analyzing various existing literature. Business intelligence can provide enormous benefits for business organizations to increase the effectiveness of business intelligence. The Internet of Things is widely used in business intelligence processes to make strategic decisions and make effective plans. Internet of things allows employees working in an organization to connect to multiple devices operating on the same network.